Analysing and reporting UK CAMHS outcomes: an application of funnel plots. Issue 3 (24th December 2014) - Fugard, Andrew J. B.; Stapley, Emily; Ford, Tamsin; Law, Duncan; Wolpert, Miranda; York, Ann
<x xml:space="preserve">Abstract</x> Background Patient‐reported outcomes measures are increasingly being used in child and adolescent mental health services (CAMHS). League tables are a common way of comparing organizations across health and education but have limitations that are not well known in CAMHS. Method Parent‐rated Strengths and Difficulties Questionnaire (SDQ) outcomes data from 15, 771 episodes of care across 51 UK CAMHS were analysed using funnel plots, an alternative to league tables. Results While most services were indistinguishable from the national average there was evidence of heterogeneous outcomes and seven services had outcomes below 99.9% limits for SDQ added‐value scores. Conclusions Funnel plots are powerful tools for navigating national data and can help prompt investigations using clinical theory and local service context. Examples are provided of factors to consider in these investigations. We argue that analyses of the local context are central to the valid application of funnel plots.